ANALISIS PENERAPAN PEMBELAJARAN TEMATIK OLEH GURU DI SDN SEMPU 2 KOTA SERANG - Fuzi Restu Fauzi; Suparno Suparno; M. Taufik (Universitas Trilogi, 2021)
The objectives of this study were (1) To describe the implementation of thematic learning by teachers in class V SDN Sempu 2 Kota Serang, (2) to describe the results of the application of thematic learning by teachers to fifth grade students of SDN Sempu 2 Kota Serang. The research took place in SDN Sempu 2 Kota Serang. Data analysis was carried out in three stages, namely: data reduction, data presentation and conclusion / verification. The results of the study: (1) the implementation of thematic learning by the teacher in class V SDN Sempu 2 Serang City has been running in accordance with the provisions of the government. During the Covid 19 pandemic, learning activities underwent changes, learning activities were carried out through 2 types of activities. There are face-to-face activities carried out by teachers visiting students' homes and learning activities carried out through the WhatsApp Group, (2) The results of the application of thematic learning by teachers to fifth grade students of SDN Sempu 2, Kota Serang, students become easier to accept the material presented, students are more active in the question and answer session, students become more character because the teacher always strengthens character through habituation activities during learning.